Epidemiološka dejavnost Zavoda za zdravstveno varstvo Novo mesto - Patkovič Colarič, Jasmina (Zdravniški vestnik, 2004)
Background. Epidemiology of communicable diseases is a preventive health activity whith the intention to prevent occurence and spreading of communicable diseases between people. Department of epidemiology of the regional Institute of Public Health take care for the Dolenjska region (Lower Carniola). Methods of work are different and some of them are described in this article. Purpose of the article is also presentation of the communicable diseases survey in the past 10 years in Dolenjska region (Lower Carniola) and comparison with the rest of the state. Conclusions. The basic activities whichhave a very important significance in prevention of incidence and prevalence of communicable diseases are health education and advice. Both of them are very much involved in every process of epidemiology of communicable diseases. The quality of work depends on mutual cooperation with health workers from other health institutions of our region and elsewhere.
Keywords: Bolezen, prijava; Cepljenje; Communicable Diseases; Dihala, infekcije; Disease Notification; Encefalitis klopni; Encephalitis, Tick-Borne; Enteritis; epidemiologija; Epidemiology; Health Education; Infekcijske bolezni; Lyme Disease; Lymska bolezen; nalezljive bolezni; Prevention And Control; Rabies Vaccine; Respiratory Tract Infections; Vaccination; Zdravstvena vzgoja; zdravstveno varstvo